C–H Functionalization of Arenes via NHC-Supported Ni/Al Bimetallic Catalysis - Jiang, Binyang; Shi, Shi-Liang (Synthesis, 2023)
Despite the C–H functionalization of arenes offering an efficient synthetic route towards functionalized aromatic compounds with high atom- and step-economy, the low reactivity of the C–H bond makes this transformation rather challenging. Compared with mono-metal catalysis, the introduction of bimetallic catalysis would greatly enhance the reactivity and selectivity of this transformation. In this review, we highlight recent progress in the C–H functionalization of arenes via NHC-Ni/Al catalysis. The added aluminum as a co-catalyst would activate arene through Lewis acid-base interaction, and regioselectivity could be controlled through the synergism of NHC-Ni and Al. This strategy could be also applied in enantioselective C–H alkylation with well-designed chiral NHC ligands.1 Introduction2 C–H Addition to Alkynes via C–H Activation3 C–H Alkylation via Ni/Al Bimetallic Catalysis3.1 Racemic Hydroarylation with Alkenes3.2 Asymmetric Hydroarylation with Alkenes4 Conclusion and Outlook
Keywords: nickel catalysis; Lewis acid; C–H functionalization; NHC ligand; bimetallic catalysis; synthetic methodology